Do macro ao micro: uma análise espacial multiescalar dos impactos da seca, as políticas hídricas e os fixos e fluxos da operação pipa no seridó paraibano - Farias, Thiago da Silva (2021)
The water is a fundamental element for the promotion of life and well-being, its availability is essential for the maintenance and development of populations, whether in supplying their basic needs or making economic activities viable. Factors such as population and economic growth have intensified the demand for water, as a result of this, the water issue has become increasingly relevant, especially in the face of the current context of climate change on the planet, intensifying the occurrence of extreme events, such as floods and droughts. Therefore, water resources management and conservation is fundamental and requires a greater attention from population and public managers, mainly in lands prone to water scarcity, these including the Brazilian semiarid (SAB), the driest region in the country. For this reason, historically, numerous public policies focusing on water storage, availability and distribution have been developed in the SAB. Among them are the dams policy promoted by DNOCS and SUDENE, the Projects of transfers between basins (PISF - Integration Program of the São Francisco River), policies for living with drought through Social Water Social Technologies - TSH (P1MC and the P1 + 2). However, in years of prolonged drought, these water works need to be complemented, and in view of this, the federal government's emergency program for the distribution of drinking water, Pipa Operation (OP), was created. The aim of this study is to conduct a multiscale spatial analysis, focus on the impacts of drought, the scope of this phenomenon and OP, in the first moment on macro-scale way, focusing on the states that compose the Brazilian semiarid region and Paraíba's State, and later in micro-regional scale, with the focus on Paraíba's Seridó, in order to deepen the consequences of drought, water policies and the actions of this emergency public policy in the region. The methodology of this work consisted of bibliographic analysis, documentary research, mapping and spatial analysis of information regarding to the Decrees of Emergency Situation and/or State of Public Calamity due to dry and drought, available through the S2iD platform, and from the OP, provided by the Northeast Military Command (CMNE), from 2012 to 2016. The data on wells and desalinators from the federal government, in addition to cisterns, obtained using Google Earth Pro images. According to the analyzed data, the drought was present in 1,483 municipalities in the states that are part of the SAB while the OP was present in 940 brazilian municipalities. In Paraíba’s state, the drought was present in 203 of the 223 municipalities. While OP was present in 173 municipalities in the state. Regarding to Paraíba’s Seridó, both, drought and OP. were present in all 15 municipalities that compose the region. In May 2016, 202 water tank trucks were in charge of transporting water to 1,361 supply points, responsible to attend 47,328 inhabitants, distributed throughout the region. These were supplied by 8 catchment points, composed by 7 reservoirs and a transposition channel, belonging both to the semi-arid region, as well as in others Paraíba’s regions. Regarding to TSH’s, Paraíba’s Seridó had 12,662, with plaque cisterns being the most common. The results indicate the scope of the OP, being fundamental for supply water to population. However, the perpetuation of this policy is emphasized, which, at first, was designed to be emergency. The TSH’s had a strong growth, especially the plaque type, demonstrating the importance of this policy in democratizing water access, as well as creating an important water reserve for local populations.